Trisect Side of Equilateral Triangle

Geometry Level 3

In an equilateral A B C \triangle ABC , the side B C BC is trisected at D D with B D = 1 3 B C BD= \frac{1}3 BC . The value of A D 2 A B 2 \dfrac{AD^2}{AB^2} can be expressed as m n \dfrac{m}n , where m m and n n are coprime positive integers. Find m + n m+n .


Source: 19th NSO Olympiad.


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Chew-Seong Cheong
Nov 17, 2016

Let the side length of A B C \triangle ABC be 1 1 and N N be the leg of altitude from A A to B C BC . N N is also the midpoint of B C BC . Then, we have:

A D 2 A B 2 = A N 2 + N D 2 1 2 By Pythagorean theorem. = ( 3 2 ) 2 + ( 1 6 ) 2 = 3 4 + 1 36 = 7 9 \begin{aligned} \frac {\color{#3D99F6}AD^2}{AB^2} & = \frac {\color{#3D99F6}AN^2+ND^2}{1^2} & \small {\color{#3D99F6}\text{By Pythagorean theorem.}} \\ & = \left(\frac {\sqrt 3}2\right)^2 + \left(\frac 16 \right)^2 \\ & = \frac 34 + \frac 1{36} = \frac 79 \end{aligned}

m + n = 7 + 9 = 16 \implies m+n = 7+9 = \boxed{16}

Nice simple application of Pythagorean theorem :)

Calvin Lin Staff - 4 years, 6 months ago

WLOG, let's assume the coordinates of A , B , C , D A,B,C,D as ( a 2 , a 3 2 ) , ( 0 , 0 ) , ( a , 0 ) , ( a 3 , 0 ) (\dfrac a 2, \dfrac {a \sqrt3} 2 ),(0,0), (a,0),(\dfrac a 3,0) respectively.

By distance formula we get A D 2 = 7 a 2 9 AD^2=\dfrac{7a^2}{9} and A B 2 = a 2 AB^2=a^2 .

Hence A D 2 A B 2 = 7 9 \dfrac{AD^2}{AB^2}=\dfrac{7}{9} .

Hence m + n = 7 + 9 = 16 m+n=7+9=16 .

wow! nice use of co-ordinate geometry:)

Rakshit Joshi - 4 years, 7 months ago
Rakshit Joshi
Nov 17, 2016

Yes there is one more possible solution, we can apply stewart's theorem: let in equilateral A B C \triangle ABC , A B = B C = C A = a AB=BC=CA = a now,

( A B 2 ) C D + ( A C 2 ) B D = B C ( A D 2 + B D × C D ) a 2 × 2 a 3 + a 2 × a 3 = a ( A D 2 + a 3 × 2 a 3 ) A D 2 = 7 a 2 9 A D 2 A B 2 = 7 9 \begin{aligned} (AB^2)CD + (AC^2)BD = BC(AD^2 + BD \times CD) \\ \implies a^2 \times \frac{2a}{3} + a^2 \times \frac{a}{3} = a( AD^2 + \frac{a}{3} \times \frac{2a}3) \\ \implies AD^2 = \frac{7a^2}{9} \\ \implies \frac{AD^2}{AB^2} = \huge \boxed { \frac{7}9 }\end{aligned}

since B D = a 3 ; C D = a a 3 = 2 a 3 \color{#3D99F6} BD= \dfrac{a}3; CD= a - \dfrac{a}3 = \dfrac{2a}{3} . sorry for incovience of diagram..

William Isoroku
Nov 21, 2016

Use area of the equilateral triangle, ratio of areas of 2 triangles = ratio of the bases of 2 triangle if they share a common height and lastly the Pythagorean theorem.

Rohan Jasani
Nov 20, 2016

Apply stewarts theorem to directly get answer

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...